Optimal capacitor placements in distribution systems: Part 2: Solution algorithms and numerical results - Chiang, H-D; Wang, J-C; Cockings, O; Shin, H-D (IEEE transactions on power delivery, 1990)
A general solution algorithm based on simulated annealing for optimal capacitor placements in distribution systems is proposed and analyzed. The solution algorithm can provide the global optimal solution for the capacitor placement problem. The solution algorithm has been implemented into a software package and tested on a 69-bus system with very promising results.